Tuberculosis: Important lessons from AOCR 2023, Bangkok, Thailand - Pakkal, Mini; Johari, Bushra; Jin , Mo Goo; Ki, Yeol Lee; Singh Sodhi, Kushaljit; Tanomkiat, Wiwatana (The ASEAN Journal of Radiology, 2023)
The Asian Symposia at the AOCR 2023 discussed the situation and role of radiology in tuberculosis. The scientific committee of the Asian Oceanian Congress of Radiology (AOCR) established the Asian Symposia in order to discuss important and relevant health topics with participating Asian radiological societies. At the AOCR 2023 Asian Symposia I: Situation and Imaging Innovation in Tuberculosis, different views, initiatives, and ideas were presented by representatives from various societies.